Tingkat Konsentrasi Belajar Anak pada Siswa Kelas IV SD melalui Brain Gym (Senam Otak) - Heni Heni; Ulvi Nurlika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of the brain gym on the level of concentration in children's learning in fourth-grade elementary school students at SDN Cimalaka II, Cimalaka District, Sumedang Regency. The research method used is a quasi-experimental design using one group pre-test and post-test design. The results showed that the average level of learning concentration in fourth-grade elementary school students before the brain gym was done was 6.18, with a standard deviation of 1.632. Meanwhile, the intermediate level of learning concentration in fourth-grade elementary school students after brain gym is done 7.01 with a standard deviation of 1.291. Bivariate analysis showed that the average increase was 7.09, evidenced by a p-value of 0.001 <0.05. In conclusion, the brain gym affects concentration in children's learning in fourth-grade elementary school students at SDN Cimalaka II, Cimalaka District, Sumedang Regency. Keywords: Brain Gym, Learning Concentration, Elementary School Students